2021
DOI: 10.3389/fncel.2021.617036
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptors in Neurodegeneration: Potential Therapeutic Applications From Basic to Clinical Approaches

Abstract: Purinergic receptors play important roles in central nervous system (CNS), where the bulk of these receptors are implicated in neuroinflammatory responses and regulation of cellular function of neurons, microglial and astrocytes. Within the P2X receptor family, P2X7 receptor is generally known for its inactivity in normal conditions and activation by moderately high concentrations (>100 μM) of extracellular adenosine 5′-triphosphate (ATP) released from injured cells as a result of brain injury or pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 214 publications
0
30
0
1
Order By: Relevance
“…In addition to the above-mentioned signaling pathway, purinergic signaling can also contribute to the activation of inflammasomes. Although it was less reported in the TBI, it has been confirmed that the activation of the P2X7 receptor contributes to the activation and proliferation of NLRP3 ( 55 ).…”
Section: Triggering Signalmentioning
confidence: 98%
“…In addition to the above-mentioned signaling pathway, purinergic signaling can also contribute to the activation of inflammasomes. Although it was less reported in the TBI, it has been confirmed that the activation of the P2X7 receptor contributes to the activation and proliferation of NLRP3 ( 55 ).…”
Section: Triggering Signalmentioning
confidence: 98%
“…ATP-dependent activation of P2X7 receptor induced microglial proliferation and activation, which resulted in neuronal cell death, cellular excitotoxicity mediated by glutamate, and activation of NLRP3 inflammasome. Consequently, pro-inflammatory cytokines were generated and released, as well as reactive oxygen and nitrogen species, both leading to the condition of neurodegeneration (Territo and Zarrinmayeh, 2021). In an AD model study, it was showed that inhibition of P2X7 receptor with antagonists could reduce the level of amyloid plaque and hinder the progression of the disease, indicating P2X7 receptor as a potential therapeutic target for neurodegenerative diseases (Rodrigues et al, 2015).…”
Section: P2x7 Receptormentioning
confidence: 99%
“…Their specific, genuine phenotypic marker is the glial fibrillary acidic protein (GFAP). Astrocytes express various DAMP and PAMP receptors, among which several Toll-like receptors (TLR) and purinergic receptors such as P2×7, which when activated by extracellular ATP, elicits neurodegeneration ( Sidoryk-Wegrzynowicz and Struzinska, 2021 ; Territo and Zarrinmayeh, 2021 ; Zhao et al, 2021 ). Beyond relative cyto-morphological uniformity of astrocytes throughout the CNS, region-specific subpopulations are being unraveled with transcriptomic approaches ( Khakh and Deneen, 2019 ; Diaz-Castro et al, 2021 ).…”
Section: Neuroinflammation: the Innate Immune Reaction Of The Central...mentioning
confidence: 99%